(untitled) (Research, Society and Development, 2021)
Introduction: COVID-19 has generated significant impacts on global health, demanding from health professionals the most adequate way to manage this disease. Among these professionals, physical therapists have an undeniable role in combating COVID-19. Objective: To analyze in the scientific literature the profile of physical therapists in hospital care in times of the COVID-19 pandemic. Methodology: A literature review of an exploratory and descriptive analytical character was carried out on technical-scientific topics, published in Brazil and abroad, on the role of hospital physiotherapists during the COVID–19. The search for articles occurred in the database from Latin American and Caribbean data on Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (PUBMED/MEDLINE) and through Scientific Electronic Library Online (SCIELO), from August to October 2021. if the following Health Sciences Descriptors (DECS): Hospital care / COVID-19/ coping / physiotherapy, then a descriptive analysis of the results was performed. Results: Five articles met the predetermined inclusion and exclusion criteria. A synoptic table was built, where knowledge was compiled after collecting information on: Author, study objective, methodology, relevant results and conclusion. Such studies show new recommendations that include safety and treatment guidelines. Conclusion: Studies show that the impacts arising from COVID-19 can provide opportunities for advances in the profile of physical therapists in the fight against COVID-19.